PENGARUH BEBAN KERJA, KEPUASAN KERJA, DAN LINGKUNGAN KERJA TERHADAP EMPLOYEE ENGAGEMENT PADA PT. BANK NEGARA INDONESIA (PERSERO) TBK KANTOR PUSAT JAKARTA KOTA - Rahael Magdalena (2024)
This research focuses on determining the influence of workload, job satisfaction, and work environment on employee engagement at PT. Bank Negara Indonesia (Persero) Tbk Head Office Jakarta City. This research uses a quantitative approach with a sample size of 75 employees using total sampling techniques. The data analysis technique used in this research is the Structural Equation Model or SEM method based on Partial Least Square or PLS. This research uses SmartPLS 4.0 software as a tool for processing data. The results of this research show that (1) workload has a positive and significant effect on employee engagement, (2) job satisfaction has a positive and significant effect on employee engagement, (3) the work environment has a positive and significant effect on employee engagement.